Preparation of Sn nano-film by direct current magnetron sputtering and its performance as anode of lithium ion battery - 赵灵智 胡社军 李伟善 侯贤华 李昌明 曾荣华 汝强 (Transactions of Nonferrous Metals Society of China, 2007)
Sn thin film on Cu foil substrate as the anode of lithium ion battery was prepared by direct current magnetron sputtering（DCMS）. The surface morphology, composition and thickness and the electrochemical behaviors of the prepared Sn thin film were characterized by scanning electron microscopy（SEM）, X-ray diffraction（XRD）, inductively coupled plasma atomic emission spectrometry（ICP）, cyclic voltammetry（CV） and galvanostatic charge/discharge（GC） measurements. It is found that the Sn film is consists of pure Sn with an average particle diameter of 100 nm. The thickness of the film is about 320 nm. The initial lithium insertion capacity of the Sn film is 771 mA.h/g. The reversible capacity of the film is 570 mA.h/g and kept at 270 mA.h/g after 20 cycles.